(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, the patterns and peculiarities of Uzbek national fabrics, the essence of the colors in them, and the types and forms of new types of pattern design are considered. Development of the silk industry in our country, continuous improvement of the processes of silkworm care and cocoon cultivation, production of raw silk, silk cocoon and effective methods of their deep processing are widely implemented. Also, it helps in the complex development of increasing the range of silk fabrics on the basis of establishing the production of ready-made silk products, increasing the export potential of the industry, and establishing a single and integrated organizational technological system that ensures the employment and income of the population in rural areas. At the same time, it increases the responsibility of artisans and weavers for their work. The long-term history and production processes of our national fabrics like “Beqasam”, “Banoras”, “Khan-atlas”, “Adras” are very complex and interesting; and the decorations are a bright reflection of the Uzbek nation. In this article, we will talk about the colors, shapes, placement and meanings of these beautiful fabric pattern designs.